Opera House Di Pekanbaru Dengan Pendekatan Eko-Arsitektur - Yanda, Gefri; Hidayat, Wahyu; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Enthusiastic people about artistry in Pekanbaru progressively increasing. It is characterized by the presence of music festivals and other art events in the frequency of routine in Pekanbaru. This phenomenon is inversely proportional to the infrastructure that supports arts activities. Beside it, performing arts venues are now insufficient to meet the needs of visitors and not the maximum in the public interest will be art. In the construction of the Opera House was not spared from its impact on the surrounding environment. Construction, operation and demolition are responsible for some of the effect that occurs in nature such as greenhouse gas emissions, declining air quality, a lack of groundwater flow and depletion of natural resources. Seeing the impact that occurs from the current development are not concerned with the environmental aspects it is fitting the concept of eco-architecture applied to the foundation of the current development. Opera House is using the concept of Eco-Building Perform meaningful combination of the results of space created from the activities and the natural surroundings which are both interconnected to create a building that can provide and benefit from the surrounding environment.Key word: Opera House, Perform Eco-Building, Eco-Architecture.